2018
DOI: 10.5152/dir.2018.17320
|View full text |Cite
|
Sign up to set email alerts
|

FSE T2-weighted two-point Dixon technique for fat suppression in the lumbar spine: comparison with SPAIR technique

Abstract: PURPOSEFat suppression magnetic resonance imaging (MRI) technique has been used to improve the diagnostic confidence in lumbar spine diseases. We aimed to compare T2-weighted water-fat separation technique (T2 Dixon) with spectral attenuated inversion recovery (SPAIR) image for fat suppression. METHODSLumbar spine MRI examinations were performed in 79 patients by using a 3.0 T machine. We compared T2 Dixon water-only image and SPAIR image for the evaluation of fat suppression quality and lesion conspicuity. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Acquiring T2-weighted DIXON sequences may allow to skip dedicated T1-weighted, T2-weighted, and STIR sequences, saving scan time and limiting the duration of time inside the scanner for trauma patients, which could limit motion artifacts related to long acquisition times. Furthermore, simultaneous to such time savings, the DIXON method could generate images with an elevated signal-to-noise ratio compared to STIR imaging and more homogeneous fat suppression [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. These advancements may increase the diagnostic yield of preoperative MRI in suspected disco-ligamentous injury; however, due to the novelty of the approach on commercially available and clinically used MRI systems, data for comparison to standard protocols is currently mostly lacking in trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Acquiring T2-weighted DIXON sequences may allow to skip dedicated T1-weighted, T2-weighted, and STIR sequences, saving scan time and limiting the duration of time inside the scanner for trauma patients, which could limit motion artifacts related to long acquisition times. Furthermore, simultaneous to such time savings, the DIXON method could generate images with an elevated signal-to-noise ratio compared to STIR imaging and more homogeneous fat suppression [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. These advancements may increase the diagnostic yield of preoperative MRI in suspected disco-ligamentous injury; however, due to the novelty of the approach on commercially available and clinically used MRI systems, data for comparison to standard protocols is currently mostly lacking in trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…T2-SPAIR is a technique combining the fat selectivity of chemical shift-selective saturation and the inversion radiofrequency pulse of short-tau inversion recovery [16].…”
Section: Discussionmentioning
confidence: 99%
“…In a study among patients showing various types of vertebral lesions (including recent fractures, spondylitis, metastasis, and haemangioma), a T2-weighted DIXON sequence showed more homogeneous fat suppression and superior lesion conspicuity when compared to imaging using spectral attenuated inversion recovery (SPAIR) [ 17 ]. For the degenerative lumbar spine, previous studies were able to demonstrate that imaging with a single sagittal T2-weighted DIXON sequence could replace the combination of dedicated T1-weighted, T2-weighted, and STIR sequences, which would not be at the expense of worsened diagnostic performance [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of bone metastases along the spine, it has recently been demonstrated that fat and water images derived from a T2-weighted DIXON sequence provide diagnostic performance similar to a protocol including standard T1-weighted sequences; thus, the fat images of the T2-weighted DIXON sequence might probably replace conventional T1weighted imaging [15,16]. In a study among patients showing various types of vertebral lesions (including recent fractures, spondylitis, metastasis, and haemangioma), a T2-weighted DIXON sequence showed more homogeneous fat suppression and superior lesion conspicuity when compared to imaging using spectral attenuated inversion recovery (SPAI R) [17]. For the degenerative lumbar spine, previous studies were able to demonstrate that imaging with a single sagittal T2-weighted DIXON sequence could replace the combination of dedicated T1-weighted, T2weighted, and STIR sequences, which would not be at the expense of worsened diagnostic performance [18,19].…”
Section: Discussionmentioning
confidence: 99%